Protein interaction, cytotoxic, transcriptomic and proteomic responses to structurally distinct EPAC1 activators in HUVECs - Jolanta Wiejak; Urszula Luchowska-Stańska; Pingyuan Wang; Jia Zhou; Pasquale Maffia; David Morgan; Graeme Barker; Stephen J. Yarwood (Scientific Reports, 2022)
Abstract The N-acylsulfonamide derivative, I942, represents the first non-cyclic nucleotide partial agonist of EPAC1. This was soon followed by the identification of the I942 analogues, PW0381, PW0521 and PWO577 and a series of benzofuran oxoacetic acid EPAC1 activators, SY006, SY007 and SY009. Protein interaction, cytotoxicity and EPAC1 activation assays applied here identify PWO577 and SY007 as being effective EPAC1 binders that are well tolerated in HUVECs at concentrations greater than 100 μM and up to 48 h incubation and are effective activators of transfected EPAC1 in U2OS cells. Using RNAseq in HUVECs we show that PWO577 and SY007 regulate approximately 11,000 shared genes, with only few differential gene changes being “off-target”. The genes significantly regulated by both PWO577 and SY007 included a subset of genes normally associated with endothelial activation, including ICAM1, MMP1 and CCL2. Of these, only the expression of MMP1 was markedly increased at the protein level, as determined by LC–MS-based proteomics. Both PWO577 and SY007 suppressed IL-6-induced STAT3 activation and associated downstream gene expression, including inhibition of SOCS3, STAT3, IL6ST and JAK3 genes. Together these results demonstrate the utility of structurally distinct, specific and non-toxic EPAC1 activators. Future modifications will be aimed at eliminating the few noted off-target effects.